Challenges and Recommendations in DevOps Education: A Systematic Literature Review - Fernandes, Marcelo; Ferino, Samuel; Kulesza, Uirá; Aranha, Eduardo (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2020: Anais do XXXIV Simpósio Brasileiro de Engenharia de Software, 2020)
Over the last years, DevOps has gained more importance and attention from the software industry, given its role in enabling continuous software delivery. As a new area, DevOps has brought significant challenges for the academy, both in terms of research topics and teaching strategies. In this paper, we present a systematic literature review that aims to identify challenges and recommendations for teaching DevOps. Our findings show a total of 73 challenges and 85 recommendations organized into different seven categories from a total of 18 papers selected. We also discuss how existing recommendations address the challenges found in the study, thus contributing to the preparation and execution of DevOps courses. Finally, we investigate if challenges and recommendations are specific for teaching DevOps.